Subsurface Drip Irrigation (SDI) for Enhanced Water Distribution: SDI - Seepage Hybrid System - Lincoln Zotarelli; Libby Rens; Charles Barrett; Daniel J. Cantliffe; Michael D. Dukes; Mark Clark; Steven Lands (EDIS)
In terms of water use efficiency, the traditional seepage irrigation systems commonly used in areas with high water tables are one of the most inefficient methods of irrigation, though some irrigation management practices can contribute to better soil moisture uniformity. Subsurface drip irrigation systems apply water below the soil surface by microirrigation, improving the water distribution and time required to raise the water table for seepage irrigation. This 6-page fact sheet was written by Lincoln Zotarelli, Libby Rens, Charles Barrett, Daniel J. Cantliffe, Michael D. Dukes, Mark Clark, and Steven Lands, and published by the UF Department of Horticultural Sciences, March 2013.